The Possibility of Equilibrium under Monopolistic Competition - Stolper, Wolfgang F. (Quarterly Journal of Economics, 1940)
Journal Article The Possibility of Equilibrium Under Monopolistic Competition Get access Wolfgang F. Stolper Wolfgang F. Stolper Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 3, May 1940, Pages 519–526, https://doi.org/10.2307/1882455 Published: 01 May 1940